Search for new phenomena in final states with large jet multiplicities and missing transverse momentum using sqrt(s) = 13 TeV proton-proton collisions recorded by ATLAS in Run 2 of the LHC - Wahlberg, Hernan Pablo (2020)
Results of a search for new particles decaying into eight or more jets and moderate missingtransverse momentum are presented. The analysis uses 139 fb−1of proton?proton collision data at √ = 13 TeV collected by the ATLAS experiment at the Large Hadron Collider between 2015 and 2018. The selection rejects events containing isolated electrons or muons,and makes requirements according to the number of -tagged jets and the scalar sum ofmasses of large-radius jets. The search extends previous analyses both in using a largerdataset and by employing improved jet and missing transverse momentum reconstructionmethods which more cleanly separate signal from background processes. No evidence forphysics beyond the Standard Model is found. The results are interpreted in the context ofsupersymmetry-inspired simplified models, significantly extending the limits on the gluinomass in those models. In particular, limits on the gluino mass are set at 2 TeV when the lightestneutralino is nearly massless in a model assuming a two-step cascade decay via the lightestchargino and second-lightest neutralino.